Standardization, Ideology and Linguistics - Armstrong, N. author. aut Link
XI, 253 p.
Keywords: The authors explore some of the ways in which standardization, ideology and linguistics are interrelated. Through a number of case studies they show how concepts such as grammaticality and structural change covertly rely on a false conceptualization of language, one that derives ultimately from standardization.